HUBUNGAN KEDUDUKAN AKHLAK DAN TASAWUF DALAM ISLAM - Rizky Almufid Anshori; Hartono; Siti Mariah; Sobirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the urgency to build a morally and spiritually balanced character among Muslims, especially in facing the challenges of modern life. In Islam, ethics (akhlaq) and Sufism (tasawuf) are two essential pillars that complement each other. Ethics represents the outward behavior of a Muslim, while Sufism is a spiritual path toward self-purification and closeness to Allah SWT. This study aims to analyze the position of ethics and Sufism in Islam, examine their interrelationship, and explore their implications in contemporary life. The research employed a qualitative descriptive method with a literature review approach. Data were collected through the analysis of relevant academic sources, including books, journals, and articles that discuss Islamic ethics and Sufism. The findings indicate that authentic Sufism naturally produces noble character. Sufi values such as sincerity (ikhlas), patience (sabr), asceticism (zuhud), and humility (tawadhu) serve as the foundation for ethical behavior. In the context of modern life—characterized by moral decline, spiritual crises, and psychological stress—the integration of ethics and Sufism proves effective in providing inner peace and shaping a balanced personality. Thus, the relationship between ethics and Sufism is both functional and synergistic: Sufism reinforces the spiritual roots of ethics, while ethics embodies the practical expression of the spiritual journey. These findings highlight the importance of Islamic education that integrates both aspects to foster a generation with strong moral and spiritual foundations. Keywords: Ethics, Sufism, Islam, Spirituality, Character Education